Sign and Hyle: Re-reading Derrida's Critique of Husserl Through the Bernau Manuscripts. Issue 50 (3rd July 2019) - Kwok, Sai Hang
ABSTRACT: Derrida's philosophy starts with a law stated in The Problem of Genesis in Husserl's Philosophy : "No analysis could present, make present in its phenomenon or reduce to the point-like nature of the element, instantaneous and identical to itself." This "law" is derived from a critique of Husserl's transcendental phenomenology, which, according to Derrida, demonstrates the impossibility of reducing phenomena to a single origin. In this paper, I argue that Derrida's critique is based on an omission of the Bernau Manuscripts, within which Husserl explores the constitution of time consciousness that is not centred at a point-like present but rather at the concatenation of Hyle. This theory surpasses the presentism in Phenomenology of the Consciousness of Internal Time and hence becomes a potential response to Derrida's criticism.